Screaming Cowbird parasitism on nests of Solitary Caciques and Cattle Tyrants - Di Giacomo, Alejandro G. (2010)
The Screaming Cowbird (Molothrus rufoaxillaris) is one of the most specialized brood parasites with only three known hosts: Baywing (Agelaioides badius), the main host throughout most of its range, and two alternative hosts in some areas of its distribution, Chopi Blackbird (Gnorimopsar chopi) and Brown-and-yellow Marshbird (Pseudoleistes virescens). We studied Screaming Cowbird parasitism in northeast Argentina where this parasite uses Baywings and Chopi Blackbirds as hosts. We monitored 69 nests of Baywings, 251 of Chopi Blackbirds, 31 of Solitary Caciques (Cacicus solitarius), and 30 of Cattle Tyrants (Machetornis rixosa). The frequency of Screaming Cowbird parasitism on Baywing nests was 80% and was 46% for Chopi Blackbirds. We recorded one event of Screaming Cowbird parasitism on one nest of Solitary Caciques and three events of Screaming Cowbird parasitism on one nest of Cattle Tyrants. The identities of parasitic eggs in both hosts were confirmed by sequencing the mtDNA control region. We propose these events of parasitism resulted from recognition errors by Screaming Cowbird females that regularly parasitize Baywings and Chopi Blackbirds. The nest of Solitary Caciques had been frequently visited by a pair of Baywings before Screaming Cowbird parasitism occurred, and the nest of Cattle Tyrants was near an active Chopi Blackbird nest that had been previously parasitized by Screaming Cowbirds.